Strategi Pemberdayaan dan Penguatan Modal Sosial Masyarakat di Era Pandemi Covid-19 - Fitriyah, Neka; Pratiwi, Apriliyanti (Riau Journal of Empowerment, 2023)
The Covid-19 pandemic has caused various social and economic problems, the impact of which is felt by the community to be extreme. The Covid-19 pandemic has caused various social and economic problems, the impact of which is felt by the community to be extreme. People who are economically weak, have acces and education in a pandemic situation are faced with groups of people we have dominat power, and have implications for unbalanced competition in socio economis life. Empowerment is one of the strategies so thet weak communities can have empowerment and are to solve problems caused by the Covid-19 pandemic voluntarily and independently.Exsploration of previous studies and literature review are strategies and techniques in constructing empowerment strategies. The results of this study indicate that empowerment must be based on the potential strength of culture, values, and local wisdom of the community. Social capital becomes energy in increasing community empowerment and capacity. The stages in the empowerment strategy that must be carried out are site selection, socialization and empowerment. The right form of empowerment in the Covid-19 pandemic era is Community Based Empowerment, while social capital can be designed to strengthen community social capital in the Covid-19 pandemic era, namely (1) Social bounding (2) Social bridging (3) Social linking. The construction of community empowerment strategies lies in the positioning of local wisdom, local potentials, individual characteristics and regional characteristics as energy in the empowerment process. The recommendations produced in this study are the need for the concept of empowerment and strengthening of social capital capacity that is implementable, measurable and leads to increased creativity and innovation of the community.